2019
DOI: 10.1186/s12913-019-4483-5
|View full text |Cite
|
Sign up to set email alerts
|

Public service motivation as a mediator of the relationship between job stress and presenteeism: a cross-sectional study from Chinese public hospitals

Abstract: Background Job stress is a strong indicator of presenteeism, but few studies have examined its diverse effects and mediators on presenteeism. This study explored the relationships between job stress, public service motivation (PSM) and presenteeism and how job stress and PSM influence presenteeism in a large national sample of Chinese healthcare workers. Methods A cross-sectional survey including 1392 healthcare workers from 11 Class A tertiary hospitals in eastern, cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…Working environments might affect the presenteeism of the aging workforces. Previously, some scholars proposed that work stress would affect presenteeism [61]. Work pressure is a part of the work environment.…”
Section: Discussionmentioning
confidence: 99%
“…Working environments might affect the presenteeism of the aging workforces. Previously, some scholars proposed that work stress would affect presenteeism [61]. Work pressure is a part of the work environment.…”
Section: Discussionmentioning
confidence: 99%
“…Challenge stress and hindrance stress had a significantly direct negative effect on PSM of healthcare workers, which differs in part from our previous hypothesis and research findings. Previous studies reported that challenge stress has a positive effect on individuals, e.g., by encouraging workers to learn and to overcome obstacles, thus benefiting career development [14,33]. We assumed that challenge stress was positively related to PSM;…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Although no studies have examined the relationship between hindrance stress and PSM, the adverse effects of job stress, especially hindrance stress, on the individual and organization have been widely discussed in many studies based on JD-R theory. These effects include burnout [35], increased presenteeism [33], and increased turnover intention [36]. Hindrance stress includes demands that are viewed by managers as unnecessary impediments to personal growth and goal attainment, and by employees as insurmountable [14].…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Two psychological conditions of workers were studied as other mediators among Chinese health care workers: affective commitment by Yang et al (2017) [24] and public service motivation by Deng et al (2019) [25]. Affective commitment and public service motivation partially mediated the associations of challenge and hindrance stress with presenteeism.…”
Section: Studies On Mediators and Pathways Of Association Between Strmentioning
confidence: 99%